Networking of Public Health Microbiology Laboratories Bolsters Europe’s Defenses against Infectious Diseases - Albiger, Barbara; Revez, Joana; Leitmeyer, Katrin Claire; Struelens, Marc J. (Frontiers in Public Health, 2018)
In an era of global health threats caused by epidemics of infectious diseases and rising multidrug resistance, microbiology laboratories provide essential scientific evidence for risk assessment, prevention and control. Microbiology has been at the core of European infectious disease surveillance networks for decades. Since 2017, these networks have been coordinated by the European Centre for Disease Prevention and Control (ECDC). Activities delivered in these networks include harmonisation of laboratory diagnostic, antimicrobial susceptilibility and molecular typing methods, multicentre method validation, technical capacity mapping, training of laboratory staff and continuing quality assessment of laboratory testing. Cooperation among the European laboratory networks in the past seven years has proved successful in strengthening epidemic preparedness by enabling adaptive capabilities for rapid detection of emerging pathogens across Europe. In partnership with food safety authorities, international public health agencies and learned societies, ECDC-supported laboratory networks have also progressed harmonisation of routinely used antimicrobial susceptibility and molecular typing methods, thereby significantly advancing the quality, comparability and precision of microbiological information gathered by ECDC for surveillance for zoonotic diseases and multidrug resistant pathogens in Europe. ECDC continues to act as a catalyst for sustaining continuous practice improvements and strengthening wider access to laboratory capacity across the European Union. Key priorities include optimisation and broader use of rapid diagnostics, further integration of whole genome sequencing in surveillance and electronic linkage of laboratory and public health systems. This article highlights some of the network contributions to public health in Europe and the role that ECDC plays managing these networks.